Biogas as a renewable energy fuel – A review of biogas upgrading, utilisation and storage. (15th October 2017) - Ullah Khan, Imran; Hafiz Dzarfan Othman, Mohd; Hashim, Haslenda; Matsuura, Takeshi; Ismail, A.F.; Rezaei-DashtArzhandi, M.; Wan Azelee, I.
Highlights: It is attempted to provide critical considerations on various biogas upgrading techniques. Membrane is an environmentally and economically sound technique for purification. Purified biogas in compressed form is a substitute of compressed natural gas for vehicles. Charged mass and compressor input work are the most important factors for storage. Abstract: Biogas upgrading is a widely studied and discussed topic and its utilisation as a natural gas substitute has gained a significant attention in recent years. The production of biomethane provides a versatile application in both heat and power generation and as a vehicular fuel. This paper systematically reviews the state of the art of biogas upgrading technologies with upgrading efficiency, methane (CH4 ) loss, environmental effect, development and commercialisation, and challenges in terms of energy consumption and economic assessment. The market situation for biogas upgrading has changed rapidly in recent years, making the membrane separation gets significant market share with traditional biogas upgrading technologies. In addition, the potential utilisation of biogas, efficient conversion into bio-compressed natural gas (bio-CNG), and storage systems are investigated in depth. Two storing systems for bio-CNG at filling stations, namely buffer and cascade storage systems are used. The best storage system should be selected on the basis of the advantages of both systems. Also, the fuel economy and mass emissions for bio-CNG and CNG filled vehicles are studied. There is the same fuel economy and less carbon dioxide (CO2 ) emission for bio-CNG. Based on the results of comparisons between the technical features of upgrading technologies, various specific requirements for biogas utilisation and the relevant investment, and operating and maintenance costs, future recommendations are made for biogas upgrading.